Efeito antidepressivo-simile da Laminarina no modelo animal de depressão induzido por Corticosterona: uma abordagem comportamental, neuroinflamatoria e in silico integradas - Nascimento, Edna Fernandes do (2025)
Depression is one of the most prevalent and disabling psychiatric disorders in the world. Studies show the association between hyperactivity of the hypothalamic–pituitary–adrenal (HPA) axis, elevated cortisol levels, and the consequent increase of pro-inflammatory cytokines, which impair serotonergic neurotransmission in the pathogenesis of depression. In this context, there is a growing search for therapeutic agents with immunomodulatory action in psychiatric disorders. Laminarin (LAM) is a beta-glucan that modulates the inflammatory response through interaction with the Dectin-1 receptor, predominant in immune system cells. However, its specific mechanisms of action remain poorly understood. Based on this assumption, this study aims to elucidate the immunomodulatory effects of laminarin in the animal model of depression induced by corticosterone (CORT). Additionally, it is proposed to perform molecular docking analyses to evaluate the affinity of laminarin for the Dectin-1 receptor and for the serotonin transporter (SERT). In a complementary way, it is intended to predict the absorption, distribution, metabolism, excretion, and toxicology (ADMET) properties of laminarin compared to fluoxetine in order to outline the pharmacokinetic profile of the beta-glucan. For this purpose, female BALB/c mice were submitted to the protocol with administration of CORT (20 mg/kg), TWEEN 0.3%, and LAM (20 mg/kg), alone or associated, for 21 days. On the 21st day, one hour after administration, the animals were subjected to the behavioral tests: open field, elevated plus maze, and tail suspension. On the 22nd day, 24 hours after the last application, the animals underwent the splash test and forced swim test. Right after the tests, the animals were euthanized and samples of hippocampus, prefrontal cortex, and striatum were collected for dosage of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α). Treatment with CORT developed depressive-like behavior in the animals, as well as provoked a pro-inflammatory effect evidenced by the increase of IL-1β and IL-6 in the brain areas. The behavioral alterations were reversed by treatment with LAM, although in the splash test antidepressant effects were not observed. In addition, treatment with LAM reduced the levels of pro-inflammatory cytokines in all brain areas when associated with CORT. Anti-inflammatory effects were also observed by LAM without the presence of CORT, being dependent on the brain area. The high affinity of laminarin for Dectin-1, evidenced by molecular docking analysis, suggests mediation of its immunomodulatory and behavioral effects by this receptor, instead of direct modulation by SERT. Moreover, the predictive ADMET analysis indicated low oral bioavailability and limited central penetration of laminarin, suggesting that its effects may be mediated by peripheral immunological modulation. Therefore, the findings of this study point to laminarin as a promising therapeutic strategy with innovative immunomodulatory properties in the treatment of depressive .